Elementary School Students' Learning Motivation Through Ludo Education Media - Rakhman, Patra Aghtiar; Andini, Novita; Islamiati, Aini; Nurrahmah, Ghina (International Journal of Education, Information Technology, and Others, 2024)
Learning motivation is a key factor that influences student success in the learning process. Without sufficient motivation, students tend to be less enthusiastic about following the material being taught and are not actively involved in class. In an effort to increase learning motivation, various innovative approaches need to be implemented.The main aim of this research is to analyze the effect of using Ludo Education on elementary school students' learning motivation. This research uses a qualitative approach with descriptive methods.The research results show that the use of Ludo Education has a positive influence on student learning motivation. Students participate more actively in learning and feel challenged to achieve the goals in the game. Ludo Education not only increases extrinsic motivation, which is based on rewards or prizes, but also motivates students intrinsically, namely based on the personal satisfaction they get from completing challenges in the game. In addition, this game helps students better understand lesson material, such as vocabulary and sentence structures in Indonesian, in a fun and interactive way.